CD40 Activity on Mesenchymal Cells Negatively Regulates OX40L to Maintain Bone Marrow Immune Homeostasis Under Stress Conditions - Bassani, Barbara; Tripodo, Claudio; Portararo, Paola; Gulino, Alessandro; Botti, Laura; Chiodoni, Claudia; Jachetti, Elena; Bolli, Niccolò; Ciciarello, Marilena; Joehrens, Korinna; Anagnostopoulos, Ioannis; Na, Il-Kang; et al. (Frontiers in Immunology, 2021)
ABSTRACT Background In the bone marrow (BM) mature T cells are maintained in homeostatic conditions, to grant the proper hematopoietic development. This homeostasis depends on a peculiar elevated frequency of regulatory T cells (Treg) and immune regulatory activities from BM-mesenchymal stem cells (BM-MSCs). In case of BM transplantation (BMT), conditioning regimen exposes the BM to a dramatic induction of inflammatory cytokines and to unbalanced T-effector (Teff) and Treg-ratio. Such unbalance negatively impacts on hematopoiesis, particularly B-cell lymphopoiesis, which require an intact cross-talk between BM-MSCs and Treg. Mechanisms through which BM-MSCs restore Treg homeostasis and the proper B-cell development are almost unknown. Methods We studied the role of host radio-resistant cell derived CD40 in restoring Teff/Treg homeostasis and proper B-cell development in murine model of BMT. We characterized the host cellular source of CD40 and performed radiation chimeras transplanting WT or Cd40-KO with WT BM also in presence of T-reg and co-infusing WT or - Cd40-KO BM-MSC. Residual host and donor T cell expansion and activation (cytokine production) as well as expression of Treg fitness markers and conversion to Th17 were analyzed. The presence of Cd40+ BM-MSC was analyzed in human setting in correlation with the frequency of B-cell precursors in patients who underwent HSCT and variably developed acute graft versus host (aGVDH) disease. Results CD40 is almost not expressed in the BM, yet Cd40-KO recipient of WT donor chimera showed impaired B-cell lymphopoiesis and Treg development. Lethal irradiation promotes CD40 and OX40L expression in radio-resistant BM-MSCs through the induction of pro-inflammatory cytokines. OX40L would favor Teff expansion and activation at the expense of Treg however the expression of CD40 dampening OX40L expression restores Treg homeostasis, granting the proper B-cell development. Indeed, opposite from dendritic cells in secondary lymphoid organs, which require CD40 trigger to express OX40L, BM-MSCs require CD40 to restrain OX40L expression. Conclusions CD40+ BM-MSCs are immune regulatory elements in the BM. Loss of CD40 results uncontrolled T cell activation because of reduced Treg, and consequently impaired B-cell development. GVHD exemplify how the loss of CD40+ BM-MSCs and the reduction in B-cell precursors, may occurs in a human setting.